2015
DOI: 10.1111/bju.13053
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Framingham cardiovascular disease risk score is associated with severity of lower urinary tract symptoms

Abstract: ObjectiveTo determine the relationship between lower urinary tract symptoms (LUTS)/benign prostatic hyperplasia (BPH) and 10-year risk of cardiovascular disease (CVD) assessed by the Framingham CVD risk score in a cohort of patients without previous episodes of stroke and/or acute myocardial infarction. Patients and MethodsFrom September 2010 to September 2014, 336 consecutive patients with BPH-related LUTS were prospectively enrolled. The general 10-year Framingham CVD risk score, expressed as percentage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…This is suggested by the elevated values of ΕΤ-1, IL-6. Secondary, the sevenfold increase in the likelihood of BOO in coronary patients suggests a possible connection between the two pathological situations, result also seen in a recent review (Russo et al, 2015). Endothelial inflammation may cause endothelial dysfunction and is a risk factor for heart disease.…”
Section: Discussion:-mentioning
confidence: 62%
See 1 more Smart Citation
“…This is suggested by the elevated values of ΕΤ-1, IL-6. Secondary, the sevenfold increase in the likelihood of BOO in coronary patients suggests a possible connection between the two pathological situations, result also seen in a recent review (Russo et al, 2015). Endothelial inflammation may cause endothelial dysfunction and is a risk factor for heart disease.…”
Section: Discussion:-mentioning
confidence: 62%
“…The mean IPSS score was 14.7±6.9 and the mean IPSS Quality index was 3.7±1.3. According to the IPSS grading, as shown in Table 3, more than half of the patients had moderately severe symptoms (range [8][9][10][11][12][13][14][15][16][17][18][19]. As mentioned in Patients and Methods, the participants had laboratory measurements of total plasma cholesterol, triglycerides, HDL and LDL, and the Atheromatous Index (A.I.).…”
Section: Results:-mentioning
confidence: 99%
“…In a recent volume of this journal, the possible association between LUTS and cardiovascular disease (CVD) was highlighted [1,2]. This topic is of interest with an ageing population.…”
Section: Referencesmentioning
confidence: 99%
“…Russo et al [1] studied the association between LUTS and CVD, by means of calculating the general 10-year Framingham CVD risk score for men with different LUTS severity, assessed with the IPSS. From their analyses, the association was apparent.…”
Section: Referencesmentioning
confidence: 99%
“…In a recent cross-sectional study in a cohort of patients with BPH/LUTS, it has been demonstrated an increase of more than 5-fold of having a Framingham risk score 10% in men with moderate-severe LUTS [13].…”
mentioning
confidence: 99%